2023
DOI: 10.1038/s42004-023-01021-1
|View full text |Cite
|
Sign up to set email alerts
|

C2-addition patterns emerging from acetylene and nickel sulfide in simulated prebiotic hydrothermal conditions

Philippe Diederich,
Alexander Ruf,
Thomas Geisberger
et al.

Abstract: Chemical complexity is vital not only for the origin of life but also for biological evolution. The chemical evolution of a complex prebiotic mixture containing acetylene, carbon monoxide (CO), and nickel sulfide (NiS) has been analyzed with mass spectrometry as an untargeted approach to reaction monitoring. Here we show through isotopic 13C-labelling, multiple reaction products, encompassing diverse CHO and CHOS compounds within the complex reaction mixture. Molecules within the same chemical spaces displayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The evolution of a complex prebiotic mixture containing C 2 H 2 , CO, and NiS was also shown in recent works by Sobotta et al and Diederich et al A suspension of precipitated NiS was shown to convert acetylene and carbon monoxide into a set of C2–4 products. Moreover, the authors demonstrated the formation of a homologous series of thioacids upon repeated addition of C 2 to the resulting compounds via acetylene.…”
Section: Acetylene In Prebiotic Chemistry Evolutionmentioning
confidence: 99%
“…The evolution of a complex prebiotic mixture containing C 2 H 2 , CO, and NiS was also shown in recent works by Sobotta et al and Diederich et al A suspension of precipitated NiS was shown to convert acetylene and carbon monoxide into a set of C2–4 products. Moreover, the authors demonstrated the formation of a homologous series of thioacids upon repeated addition of C 2 to the resulting compounds via acetylene.…”
Section: Acetylene In Prebiotic Chemistry Evolutionmentioning
confidence: 99%